Kropotkin : reviewing the classical anarchist tradition - Kinna, Ruth (Edinburgh University Press, 2016)
A sympathetic critical analysis that dispels myths and highlight the importance of Kropotkin's anarchist thought. Kropotkin has been celebrated as the most accessible and coherent of the classical anarchists. In this book, Ruth Kinna provides a new interpretation of Kropotkin, removing his ideas from the 'classical' tradition and situating them in a critique of classical anarchism. By looking at his collaborations with other leading writers in the movement, Kinna shows how Kropotkin understood anarchist traditions while revealing how the Russian revolutionary movement shaped his anarchist, communist politics. This analysis corrects some popular myths about Kropotkin's thought, highlights the important and unique contribution he made to the history of socialist ideas and sheds new light on the nature of anarchist ideology.